2018
DOI: 10.3390/su10093151
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Monitoring and Audit Quality: Evidence from Korea

Abstract: This study investigates the effects of both foreign majority shareholders and foreign investors’ participation in the board of directors on audit quality, as reflected by auditor size and audit fees. In addition, the study examines the moderating effect of an agency problem on the relationship between foreign investors and the monitoring of audit quality. Using 1574 non-financial firm-year observations listed on the Korea Stock Exchange from 2000 to 2003, we find that the presence of foreign investors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 65 publications
1
25
0
2
Order By: Relevance
“…Beuselinck, Blanco and García Lara examined the role of FOOWN in enhancing the quality of accounting information and found that increases in FOOWN led to increases in the quality of financial reporting [89]. Lee, Rhee and Yoon explored the effects of both foreign majority stakeholders and foreign investors' participation on the board of directors on audit quality and establish that the presence of foreign investors such as foreign block stakeholders and foreign outside directors increased audit quality [38]. An studied how FOOWN affects the quality of financial reporting of firms listed on the Korean Stock Exchange and observed that FOOWN is positively linked with the quality of financial reporting.…”
Section: Foreign Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Beuselinck, Blanco and García Lara examined the role of FOOWN in enhancing the quality of accounting information and found that increases in FOOWN led to increases in the quality of financial reporting [89]. Lee, Rhee and Yoon explored the effects of both foreign majority stakeholders and foreign investors' participation on the board of directors on audit quality and establish that the presence of foreign investors such as foreign block stakeholders and foreign outside directors increased audit quality [38]. An studied how FOOWN affects the quality of financial reporting of firms listed on the Korean Stock Exchange and observed that FOOWN is positively linked with the quality of financial reporting.…”
Section: Foreign Ownershipmentioning
confidence: 99%
“…Sachs and Warner contended that FOOWN undertakes vital roles in supervising management, in same as the roles performed by large external stakeholders in emerging economies since the foreign owners have positive incentives to safeguard their capital investment [40]. The higher the number of shares managed by foreign partners, the more the foreign partner allots managerial places in the corporate to foreigners, either on the board of commissioners or a board of directors, which aim at aligning the interests of management and stakeholders to enhance the quality of financial reports [5,41,38]. All these lead to improved quality of financial reporting thereby decrease the prospect of a corporate obtaining a modified audit opinion.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that earnings quality is one of the key factors associated with corporate sustainability. Therefore, from the sustainability view, prior studies have investigated earnings quality and how market participants react differently to the quality of earnings [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, auditor changes can be motivated by opportunistic incentives under ineffective governance mechanisms. Using 1574 sample firm-years of Korean data in the period of 2000-2003, Lee et al [46] report that the presence of foreign investors and outside directors is positively associated with the likelihood of choosing Big 4 auditors and paying higher audit fees. Beasley and Petroni [28] report evidence that independent boards tend to select industry specialized auditors.…”
Section: Auditor Change and Governance Mechanismmentioning
confidence: 99%